Amination of epoxides as a convenient approach for lipophilic polyamines synthesis - E. A. Eshtukova-Shcheglova; K. A. Perevoshchikova; A. V. Eshtukov-Shcheglov; D. A. Cheshkov; M. A. Maslov (Тонкие химические технологии, 2022)
Objectives. Alkylated derivatives of polyamines are able to block the growth of cancer cells due to their embedding into the polyamine biosynthesis mechanisms. The study aimed to synthesize lipophilic derivatives of norspermine or triethylenetetramine based on the formation of a C–N bond during the opening of the oxirane ring by primary amines to expand a number of synthetic polyamine derivatives with antitumor activity.Methods. The starting compounds—glycidol alcoholate or epichlorohydrin—were reacted with hexadecyl bromide or sodium hexadecanolate to give glycidyl hexadecyl ether. The key reaction for the preparation of lipophilic polyamines was the amination of lipophilic epoxides with polyamines in the presence of calcium triflate. Acylation of the hydroxyl group formed during the opening of oxirane was carried out by the action of 4-dimethylaminopyridine and acetic anhydride. The introduction of an alkyl substituent in the presence of sodium hydride led to intramolecular cyclization with the formation of an oxoazolidine cycle. The regioselectivity of the oxirane ring opening reaction at the C(1) position of glycerol was confirmed by two-dimensional heteronuclear {1H,13C} nuclear magnetic resonance spectroscopy.Results. An approach to the synthesis of novel lipophilic polyamines based on the catalytic amination of epoxides was developed and tested. Compounds based on norspermine and triethylentetramine containing a hydroxyl group at the C(2) atom of the glycerin backbone were obtained. For norspermine derivatives, the hydroxyl group was modified: an acetyl substituent was introduced and a derivative containing an oxoazolidine cycle was obtained.Conclusions. The obtained lipophilic polyamines can be considered as potential antitumor agents, for which cytotoxicity against various cancer cells will be evaluated in the future.